The Utilization of Loose Parts Play Media in Early Childhood Pre-Mathematics Learning - Endang Endang; Destarina Arghia Lurselina Dewi; Sintha Wahjusaputri; Amelia Vinayasri (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
Loose parts media is a creative and effective learning media for early childhood, especially in supporting the development of pre-mathematics skills. This study aims to analyze the use of loose parts media in learning pramathematics through play. The research method used is descriptive qualitative through direct observation of 4-5 years old totaling 10 children, interviews with teachers and principals, and analysis of related documents in the form of teacher's daily journals. The results of this study show that loose parts media is effectively used to improve children's cognitive abilities in logical thinking in recognizing patterns, classifying objects, and understanding basic math concepts such as numbers and shapes. This activity also stimulates creativity, exploration and collaboration between children in a fun learning atmosphere. Based on these findings, it is recommended that educators use loose part game media in daily learning activities to enrich early childhood learning experiences, especially in the field of pre-math. This research can improve logical thinking skills by manipulating loose parts in solving problems, developing cognitive and analytical skills early on in teaching premathematics, and developing more varied teaching strategies in utilizing the use of loose parts media through games.